Practice of Pre-Death Property Distribution among Muslim Communities in Cirebon from the Perspective of Islamic Law and Legal System - Setyawan, Edy; Yasin, Ahmad Alamuddin; Himam, Achmad Samil (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
In Islam, the division of wealth refers to the process of transferring ownership of assets from the owner to specific recipients, either with specific portions or without division. Although wealth distribution typically occurs after the death of the owner, there are practices where distribution takes place before death. This research aims to analyze the patterns of pre-death wealth distribution within community families in Cirebon, as well as the perspectives of heirs on such practices and their implications on property ownership laws according to Islamic principles and other legal systems. The research methodology employed is qualitative, using a case study approach to explore pre-death wealth distribution practices among community families in Cirebon. The legal system framework theorized by Lawrence Friedman, including legal structure, legal substance, and legal culture, serves as the approach and perspective in this study. The research findings indicate that the legal structure within these families involves the owner distributing wealth to heirs according to local traditions. The legal substance involved in this distribution is inheritance division, although from an Islamic law perspective, such distribution may be considered as gifts or bequests. The legal culture of pre-death wealth distribution is influenced by various factors, including efforts to prevent conflicts among heirs after the death of their parents. Despite being categorized as gifts or bequests in Islamic law, this system of wealth distribution is seen as a solution to avoid disputes in wealth distribution among Muslim communities in Cirebon.